“The Role Of Clinic Development Strategies In Enhancing Care Coordination And Clinical Workflow: A Systematic Evaluation Of Evidence” (The Review of Diabetic Studies, 2024)
Clinic development strategies have become a central focus of modern healthcare transformation, driven by the need to improve care coordination, streamline clinical workflows, and strengthen patient outcomes. This systematic evaluation synthesizes evidence from studies published between 2016 and 2025 to determine how organizational, technological, and process-oriented development strategies influence coordination mechanisms, interdepartmental collaboration, patient flow, and clinical efficiency. Using PRISMA-guided procedures, databases including PubMed, Scopus, Web of Science, and CINAHL were searched for empirical, experimental, and mixed-method studies analyzing clinic development initiatives. Results indicate that structured workflow redesign, digital health integration, multidisciplinary care models, and capacity-building programs significantly reduce waiting times, enhance communication between providers, and increase adherence to clinical guidelines. Findings also highlight that clinics adopting standardized protocols, Lean-based process improvements, and interoperable health information systems report measurable gains in patient satisfaction, reduced errors, and better continuity of care. The review concludes with a proposed evidence-driven model for clinic development that aligns operational performance with patient-centered goals.